Rascal - Miles, Ellen (New York : Scholastic, 2007)
Lizzie and Charles Peterson love dogs, especially puppies. So it is perfect that the Peterson's are a foster family for young dogs. The Peterson's newest foster puppy is Rascal. He is a Jack Russell terrier, and his name fits him well. He may be small, but he can cause big trouble. Lizzie and Charles are in for a challenge. Will they be able to find someone who will care for this pesky little puppy?
3-6
600L
N
3.9
Keywords: Puppies -- Juvenile fiction; Jack Russell terrier -- Juvenile fiction; Dogs -- Juvenile fiction; Dog rescue -- Juvenile fiction; Foster care of animals -- Juvenile fiction; Puppies -- Fiction; Dogs -- Fiction; Animals -- Infancy -- Fiction; Puppies -- Fiction; Jack Russell terrier -- Fiction; Dog adoption -- Fiction